Reflection on the Ethics of Educator Accountants in the Concept of Life Philosophy of Ki Hajar Dewantara - Sari, Mega Devita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to test the suitability of educator accountant ethics with the concept of Ki Hajar Dewantara's philosophy of life. The study uses literature study by harmonizing the concept of Ki Hajar Dewantara's philosophy of life with the Indonesian Accountant Code of Ethics. The type of data used comes from secondary data obtained from various literature, both print and digital. Data collection techniques are carried out by means of documentation. The data analysis method used in this study is the content analysis by checking between libraries and rereading libraries. The results of this study show that the concept of Ki Hajar Dewantara's philosophy of life in the form of Trihayu is realized when the educator's accountant is able to maintain self-safety both soul and mind so that he will have strong integrity in his work, the Trisakti Jiwa concept is carried out in the form of developing creativity, creativity and being able to understand the sense of being able to build motivation for his work, Next concept Trilogy Leadership can take the form of providing a good example for prospective accountants later, and the last concept in the form of Tripantangan can prevent educator accountants from unethical actions and the concept is in accordance with the Indonesian accountant code of ethics.